COMPARATIVE STRENGTH CALCULATIONS COMPRESSED CONCRETE ELEMENTS BASED ON DEFORMATION MODELS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The comparative calculation of durability of the compressed reinforce-concrete elements in normal sections is executed on the basis of existent deformation models of EN-2, ДБН В.2.6. 98:2009 and ДСТУ Б В.2.6 156: 2010 and also to the deformation model with the extreme criterion of durability. The results of calculations in the above deformation models are compared with the experimental researches. Keywords: concrete, armature, deformation model, durability, deformation, normal section, reinforce-concrete element, extreme criterion.